Commemorative plaque with project cost - Ghosh, Ayan (2023)
Commemorative plaque dedicated to Frederick W. Stevens as the designer and superintendent of the Municipal Buildings. Below Stevens is his assistant and resident engineer, Rao Sahib Sitaram Khanderao, who would later design (with DN Mirza) the Taj Mahal Palace Hotel. Also mentioned is Grattan Geary, who was the President of the Corporation and a friend of Stevens. Stevens had designed Geary's private villa at Lonavala.